FEATURES OF THE ENTERPRISE DEVELOPMENT MANAGEMENT DURING THE CRISIS - Kasianova, Nataliia (Proceedings of National Aviation University (archive), 2016)
In the article the key moments in the development of the economic system were described, the problem of determining bifurcation points was solved and, on this basis the trajectory of the enterprise was chosen. The essence and characteristics of enterprise development management during the crisis was overviewed. A choice of methodological support development strategy was made based on a study of possible trajectories. Practical aspects of business management in the proposed methodologies were scientifically reasoned.